Implementation of DCT with Xilinx Virtex / Muhamad Ridzuan Hashim - Hashim, Muhamad Ridzuan (2007)
This project is about the implementation of DCT with xilinx virtex. Xilinx virtex is used to simulate and implement the discreet cosine transform (DCT) circuit. The outcome of this project will be the process to show how an image from sender will be compress into pixel values into DCT values. Then it will be change from pixel values into image to the receiver in a network. This phenomenon is much related of using the software xilinx ISE 9.2i to implement the DCT. The process will involve synthesizing, analyzing, and studying the DCT to simulate and compare it with the MATLAB simulation using the xilinx virtex FPGA program